Behaviour of RC columns strengthened with SCC-filled steel tubes under cyclic loading. (15th November 2019) - Yan, Yuhong; Liang, Hongjun; Lu, Yiyan; Liu, Zhenzhen; Gong, Tianniu
Highlights: Seismic behaviour of RC column strengthened with SCC-filled steel tube was studied. The failure modes, ultimate load and energy dissipation were evaluated. The influence of parameters was investigated by a parametric study. Abstract: The behaviour of RC columns strengthened with self-compacting concrete (SCC)-filled steel tubes under cyclic loading was experimentally and numerically investigated. Fourteen strengthened columns and one un-strengthened RC column were tested. The parameters studied for the strengthened columns were the diameter–thickness ratio, axial load ratio, and concrete strength. Experimental results showed that the strengthened columns performed significantly better than un-strengthened columns with regard to seismic properties. With the decrease in the diameter–thickness ratio, the ultimate lateral load, ductility, and energy dissipation capacity of the strengthened columns were remarkably improved. The ultimate lateral load and energy dissipation capacity at the axial load ratio of 0.30 were higher than that at 0.07, 0.15, and 0.45. The strength of the post-poured concrete had a negligible effect on seismic properties. Besides the tests, a finite element model was established by ABAQUS and a computer program is compiled to predict the envelope curves based on fiber element method. The accuracy and reliability of the FE models were validated by comparing the calculated and test results. In the subsequent parameter study, it was found that, compared with other parameters, the decrease in the diameter–thickness ratio had the greatest effect on the improvement of seismic properties. The increases in steel yield strength and post-poured concrete strength did not result in significant improvement in strengthening but raised the cost. The strengthened column would take the highest ultimate lateral load when the axial load ratio was close to 0.30. The calculated results of the computer program were proved accurate so that it can be used for guiding engineering practice.